High‐Loading Single‐Atom Copper Catalyst Supported on Coordinatively Unsaturated Al2O3 for Selective Synthesis of Homoallylboronates. Issue 12 (12th May 2020) - Guo, Tenglong; Tang, Nanfang; Lin, Feng; Shang, Qinghao; Chen, Shuai; Qi, Haifeng; Pan, Xiaoli; Wu, Chuntian; Xu, Guoliang; Zhang, Jian; Xu, Dezhu; Cong, Yu
Abstract: Single‐atom catalysts (SACs) as a bridge between hetero‐ and homogeneous catalysis have attracted much attention. However, it is still challenging to generate stable single atoms with high metal loadings, and the application of SACs in traditionally homogeneous catalytic reactions is highly desirable. Herein, a Cu SAC with a high Cu loading of 8.7 wt % supported on coordinatively unsaturated Al2 O3 was prepared and used in the amine‐free synthesis of homoallylboranes. Up to 99 % conversion, 95 % 1, 4‐selective boration of the enals, and 48–68 % isolated yields of homoallylboranes were achieved, equaling the results of reported homogenous catalysts, and the system was more efficient and stable than nano Cu/γ‐Al2 O3 . Mechanistic investigation indicated that Cu‐Bpin species are the active intermediates of selective boration. The superior catalytic and recycling performance of Cu SAC paves an efficient and green path toward selective synthesis of homoallyborane fine chemicals. Abstract : (I Can't Get No) Saturation : A Cu single‐atom catalyst with a high Cu loading of 8.7 wt % supported on coordinatively unsaturated Al2 O3 is prepared and used in the amine‐free synthesis of homoallylboranes. Up to 99 % conversion, 95 % 1, 4‐selective boration of the enals, and 48–68 % isolated yields of homoallylboranes were achieved, equaling the results of reported homogenous catalysts.